Activity and Structural Characteristics of Peach Gum Exudates. (3rd June 2018) - Yang, Haiyan; Wang, Dawei; Deng, Jia; Yang, Jing; Shi, Chun; Zhou, Fanglang; Shi, Zhengjun
Abstract : Polysaccharide fractions were prepared from peach gum exudates by treatments with alkaline hydrogen peroxide (AHP) and liquid hot water (LHW). The structural characteristics and activities of the polysaccharide fractions were comparatively studied. The results suggested that arabinogalactans substituted with xylose and uronic acids were the main structure of all polysaccharide fractions. AHP and LHW treatments introduced the degradation of the polysaccharides, reducing the molecular weight of polysaccharides from 182500 g/mol to 78450 g/mol and 68420 g/mol, respectively. The decreasement of molecular weights responded to the decrease of thermal stability of polysaccharide fractions. However, AHP and LHW treatments removed most of the nonsugar composition, increasing the DPPH - and ABTS + -scavenging activity of polysaccharides. Polysaccharide fractions obtained from LHW treatment showed favorable DPPH - and ABTS + -scavenging activity at 22.9% and 34.3%, respectively, at concentration of 1000 μ g/mL.